Gut Microbiota and Bone Diseases: A Growing Partnership - Chen, Yu; Wang, Xin; Zhang, Chunlei; Liu, Zhiyong; Li, Chao; Ren, Zhigang (Frontiers in Microbiology, 2022)
Gut microbiota is key to human health and disease. Convincing studies have demonstrated that dysbiosis in the commensal gut microbiota is associated with intestinal and extra-intestinal diseases. Recent explorations have significantly contributed to the understanding of the relationship between gut microbiota and bone diseases (osteoporosis, osteoarthritis, rheumatoid arthritis, and bone cancer). Gut microbiota and its metabolites may become associated with the development and progression of bone disorders owing to their critical role in nutrient absorption, immunomodulation, and the gut–brain–bone axis (regulation hormones). In this work, we review the recent developments addressing the effect of gut microbiota modulation on skeletal diseases and explore a feasible preventive approach and therapy for bone diseases.